Begonia muricata Blume and Begonia serratipetala Irmsch durability as indoor pot plant in Eka Karya Bali Botanic Garden - Siti Fatimah Hanum; Ayyu Rahayu; I Dewa Putu Darma (The East Java Biological Society, 2021)
Begonia is very popular as a foliage plant and some begonia species grow up in pots. Begonia serratipetala and Begonia muricata are Indonesian begonia species that are well suited as indoor potted plants because of their leaf color and shape. In addition, the Bali Botanical Garden's landscape nursery would like to use these begonias for decoration in all buildings. However, it still needs to be studied how long the shelf life of the two begonias is in indoor environments in the highlands without air conditioning (AC). The aim of this study was to investigate the indoor shelf life of B. serratipetala and B. muricata. This research method consists of two steps. The first step was the acclimation phase and the second step was the indoor placement phase. Each begonia was repeated three times. Parameters studied included plant growth (plant height, leaves, leaf width, and leaf length) and environmental factors (sunlight intensity, air temperature, and humidity). The data were analyzed descriptively. Correlation analysis was used to determine the relationship between growth parameters and environmental factors. The result showed that both begonias (B. muricata and B. serratipetala) have similar persistence to indoor begonia species within two weeks, the ideal time for plant replacement